2020
DOI: 10.1128/aac.02115-19
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing the Antiamoebic Drug Diiodohydroxyquinoline for Treatment of Clostridioides difficile Infections

Abstract: Clostridioides difficile, the leading cause of nosocomial infections, is an urgent health threat worldwide. The increased incidence and severity of disease, the high recurrence rates, and the dearth of effective anticlostridial drugs have created an urgent need for new therapeutic agents. In an effort to discover new drugs for the treatment of Clostridioides difficile infections (CDIs), we investigated a panel of FDA-approved antiparasitic drugs against C. difficile and identified diiodohydroxyquinoline (DIHQ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 53 publications
1
31
0
Order By: Relevance
“…A time-kill assay was performed for dorzolamide and linezolid against E. faecium HM-952, following a method described previously ( Abutaleb & Seleem, 2020a ; Abutaleb & Seleem, 2020c ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A time-kill assay was performed for dorzolamide and linezolid against E. faecium HM-952, following a method described previously ( Abutaleb & Seleem, 2020a ; Abutaleb & Seleem, 2020c ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, VRE infections are associated with increased rates of mortality as well as high economic burden due to extended periods of hospitalizations ( Stagliano et al, 2017 ). The U.S. Centers for Disease Control and Prevention (CDC) recently reported that VRE infections contributed to nearly 55,000 hospitalizations in the United States in 2017, which resulted in a 10% mortality rate and cost nearly $540 million in healthcare costs ( Abutaleb & Seleem, 2020c ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimum bactericidal concentration (MBC) of these drugs was tested by plating 4 µL from wells with no growth onto chocolate agar II plates. Plates were then incubated at 37 ° C in the presence of 5% CO 2 for 24 h. The MBC was categorized as the lowest concentration that reduced bacterial growth by 99.9% [ 45 , 46 , 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…Plates were incubated at 37 ° C for at least 18 h before recording the MBC. The MBC was categorized as the lowest concentration that reduced bacterial growth by 99.9% [ 45 , 46 , 47 ].…”
Section: Methodsmentioning
confidence: 99%